Lipid–Protein Oxidation and In Vitro Digestibility of Fermented Turkey Sausages as Affected by Lipid Formulation. Issue 10 (7th September 2022) - Serdaroğlu, Meltem; Öztürk‐Kerimoğlu, Burcu; Zungur‐Bastıoğlu, Aslı; Kavuşan, Hülya Serpil; Ötleş, Semih; Özyurt, Vasfiye Hazal
Abstract: This research investigates the effects of using different lipid formulations (100% beef fat, 85% beef fat+15% olive oil, or 70% beef fat+30% olive oil) in fermented turkey sausages on protein–lipid oxidation, in vitro digestibility, and related quality parameters. The use of olive oil results in decreased fat content, modified fatty acid profile, and increased pH value, acidity, and water activity, besides changes are recorded in instrumental quality and sensory features. Lipid oxidation is higher in samples with 30% olive oil than in the others. Carbonyl content increases depending on oil level and storage time. α‐aminoadipic semialdehyde is only detected in products containing 30% olive oil and their concentrations increased with storage. γ‐glutamic semialdehyde also increases by olive oil inclusion, but decrements are recorded during storage. Increasing olive oil results in increased pepsin digestibility but losses are recorded in both pepsin and trypsin plus α‐chymotrypsin digestion rates during storage. Practical applications : Inclusion of vegetable oils into meat product formulations has been preferred recently to supply healthier products, but in this situation, oxidative deterioration again becomes a considerable problem affecting overall quality. The data obtained from the present work wil contribute to understand the impacts of formulation and processing operations on the formation of oxidation products and change in digestibility, thereby to pioneer further research on this topic. Abstract : Protein–lipid oxidation and digestibility of fermented sausages are assessed. Carbonyls and semialdehydes are higher in samples containing 30% olive oil. Peroxide and two‐thiobarbituric acid reactive substances (TBARS) values increase in sausages with higher levels of olive oil. Olive oil usage increases pepsin digestibility, however, during the storage digestibility loss is recorded. Utilization of olive oil alters chemical, instrumental, and sensory quality.